Small Islands Landscape Use Mapping and Its Patches Spatial Structure Analysis at Parang Islands, Karimunjawa National Park, Indonesia - Muhammad Helmi; Nurfatin Adibah; Rikha Widiaratih; Hariyadi Hariyadi; Ibnu Pratikto (Indonesian Journal of Oceanography, 2020)
The results of small islands landscape ecology analyses within remote sensing science are not widely discovered on the inferential capabilities of such research. This issue presents a series of papers on the use of landscape ecology techniques to explore the landscape use and its patches spatial structure patterns. The aim of this research are to map the landscape use patches based on GeoeEye-1 high resolution satellite image and to assess its patches spatial structure. This prototype research was conducted at Parang Islands, Karimunjawa National Park that was inhabitant and used for complex anthropogenic activities long time before the national park status establish. Significant accuracy for landscape use map has done using overall accuracy, producer and user accuracy, and Kappa index methods. The analyses focus on the variation and composition of landscape use and the value of its patch spatial structure to dealing with national park policy and management.